PRIVATIZATION OF CESU AS A SUSTAINABLE TOOL FOR REDUCING AT&C LOSS - Nanda, Suresh Chandra (International Journal of Psychosocial Rehabilitation, 2020)
The study focuses and enlighten the management to explore advantages of the privatization of power sector erstwhile central electricity supply utility of orissa .The Distribution sector is the most challenging and worst performer in the present context.The utility witnessed AT&C Loss 30.49%,Distribution Loss 28.15% as per FY 2018-19 .Due to absence of Tariff revision of consumer tariffs followed by rise in power purchase cost, Establishment cost, Employee Cost due to implementation of 7th pay revision coupled with inadequate reduction of AT&C losses has serious financial implication on the sustainability and viability of utility in the future investment and capacity addition front.It is imperative to restore the financial position healthy,minimizing Transmission Distribution loss,cash flow maintenance, operation ,reliability powersupply ,upgrading Distribution network.uninterrupted supply to regulated consumers,improved customer satisfaction.The objective is to ensure zero power cut,Reduced Transmission and Distribution losses,affordable tariff consistent with electricity Act.This will enable consumer protection, significant improvement in voltage supply and consumer interface. .The Utility is committed to ensure capital Investment for improving operational efficiency by augmenting transformer capacity network,added value addition by eliminating power theft,poor maintenance,Replacement of old age conductor,installation of smart meter, prepaid meter,modern transmission system..Both primary and secondary data interview,questionnaire has been collected and indepth analysis done to contribute how the Operation will efficiently make the utility commercially viable and will be growth engine for both industrial and agricultural sector of the state.This article will provide new dimension and academic support to make the power utility vibrant,efficient,and bring down the AT&C loss to 15% FY 2028.